Mapping genes governing flower architecture and pollen development in a double mutant population of carrot - Budahn, Holger; Barański, Rafał; Grzebelus, Dariusz; Kiełkowska, Agnieszka; Straka, Petra; Metge, Kai; Linke, Bettina; Nothnagel, Thomas (Frontiers in Plant Science, 2014)
A linkage map of carrot (Daucus carota L.) was developed in order to study reproductive traits. The F2 mapping population derived from an initial cross between a yellow leaf (yel) chlorophyll mutant and a compressed lamina (cola) mutant with unique flower defects of the sporophytic parts of male and female organs. The genetic map has a total length of 781 cM and included 285 loci. The length of the nine linkage groups (LGs) ranged between 65 and 145 cM. All LGs have been anchored to the reference map. The objective of this study was the generation of a well-saturated linkage map of D. carota. Mapping of the cola-locus associated with flower development and fertility was successfully demonstrated. Two MADS-box genes (DcMADS3, DcMADS5) with prominent roles in flowering and reproduction as well as three additional genes (DcAOX2a, DcAOX2b, DcCHS2) with further importance for male reproduction were assigned to different loci that did not co-segregate with the cola-locus.